Pelalawan Convention And Exhibition Centre Dengan Pendekatan Arsitektur Kontemporer - Dariyanto Dariyanto; Gun Faisal; Pedia Aldy (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Pelalawan currently does not have facilities that can accommodate the visitors in large quantities to conduct an activity in the form of exhibitions or promotions for the introduction and develop the potential of the area. Developments in the world of trade, industry, tourismand agriculture are the points for development that bring foreign exchange in Pelalawan. The presence of Pelalawan Convention and Exhibition Centre in hopes of fulfilling the needs ofthe event organizers will be wider place, add value to the community and as a place to gather business people and provide facilities For Convention and exhibition activities. The researchmethods on this design are by conducting data collection, library studies and empirical studies. The concept of the conception based on the observation method of the design function is the Convention as a symbol of mutual agreement in cooperation relationship both parties. This building is designed with the approach of contemporary architecture in order to display the imagery and identity of Pelalawan regency with an attractive design to be a symbol of the grandeur of the building Pelalawan Convention and Exhibition Centre. The main facilities of this building are the Convention hall, Exhibition hall, as a place to gatherthe visitors and business people. The facilities are the meeting room, training room and Food Court.Keywords: Convention and Exhibition, Shake Hands, Contemporary Architecture